The Impact Of Artificial Intelligence Technology On The Accounting Profession - Sri Mulyati; Lestari, Syifa Puji; Bt. Ab. Hadi, Siti Hajar (Universitas Pamulang, 2024)
The aim of this research is to determine the impact of the usefulness and convenience of artificial intelligence technology on the accounting profession based on the perspective of accounting students. This research includes survey research with questionnaires. The population in this study were 100 students from the Accounting Study Program at STIE Sutaatmadjha Subang and Islamic University Antarbangsa Selangor Malaysia. Sampling used the purposive sampling method. The sample in this study was 74 Accounting students from STIE Sutaatmadjha Subang and 26 Accounting students from the Islamic University Antarbangsa Selangor Malaysia. The data analysis technique uses Linear Regression Analysis techniques and independent simple t-test. The results of this research show that the usefulness and convenience of artificial intelligence have a positive effect on the accounting profession. The magnitude of the influence of the usefulness and convenience of Artificial Intelligence technology on the accounting profession is 33.5%.